Adoption of tax digitalisation among Malaysian tax practitioners - Maheran Zakaria; Wan Noraswaniaty Wan Ahmad; Nuraini Che Hussin; Rabaatul Azira Hassan; Marziana Madah Marzuki; Muhammad Syukur; Eka Nurmala Sari (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2024)
The rapid advancement of digitalization has significantly impacted various aspects of accounting professions, particularly in taxation. Tax digitization offers numerous advantages, including streamlining tax processes, reducing administrative burdens, increasing efficiency, and enhancing data security. While tax practitioners in advanced economies have embraced digitalization, their Malaysian counterparts are still in the early stages of transitioning to a modern digital system. This situation has prompted researchers to predict factors that could accelerate the adoption of tax digitalization among Malaysian tax practitioners. Emulating the Unified theory of acceptance and use of technology (UTAUT), this study investigates the adoption of tax digitalization with performance expectancy, effort expectancy, social influence, and facilitating conditions. The researchers distributed 200 questionnaires to Malaysian tax practitioners. However, only 142 proceeded for further analysis. Results from multiple regression using partial least squares structural equation modelling (PLS-SEM) 3 indicate that all variables: effort and performance expectancy, social influence, and facilitating conditions exhibit a significant relationship with tax digitalization adoption. These findings provide valuable insights for policymakers, tax authorities, and professional bodies in developing strategies and initiatives to promote the adoption of tax digitalization among practitioners. Embracing digitalization is crucial for transforming the profession and fostering efficiency, sustainability, and resilience.